Budowa budynku gospodarczego, wiaty, altany, oranżerii (ogrodu zimowego) i obiektów małej architektury na podstawie zgłoszenia - Sługocka, Martyna; Bursztynowicz, Michał (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
In the present paper, the authors look closer, as described in the Act – Construction Law, to the institution of notification of the intention of building on the example application built outbuilding, sheds, gazebos, conservatory (winter garden) and landscape architecture. The institution notification of the construction is in fact a derogation from the general rule of construction law, under which construction works can start only on the basis of a final decision on the construction permit. The study has examined the concept used by the legislature. Additionally, the authors discussed the procedure for notification of the intention of works. The article reference both to literature, as well as to the rich jurisprudence of administrative courts. In the last part of this work the authors present proposals to amend the current legislation.
Keywords: zgłoszenie; pozwolenie; budownictwo; prawo budowlane